2022
DOI: 10.1097/gme.0000000000001950
|View full text |Cite
|
Sign up to set email alerts
|

The association of age at natural menopause with pre- to postmenopausal changes in left ventricular structure and function: the Coronary Artery Risk Development in Young Adults (CARDIA) study

Abstract: Objective: The association between menopause and incident cardiovascular disease (CVD) is controversial. We evaluated the relationships of estrogen deficiency (ovarian reproductive aging) assessed by age at natural menopause (ANM), chronological aging, and antecedent CVD risk factors (biological aging) with left ventricular (LV) structure and function among women transitioning from pre-to postmenopause.Methods: We studied 771 premenopausal women (37% Black) from the Coronary Artery Risk Development in Young Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Since the parameters of LV function are affected by individual differences [ 46 , 47 ], we analyzed the PCAT and LV function parameters by partial correlation analysis to exclude the effects of interference factors. There was no correlation between PCAT and LV function parameters, but a significant correlation between FAI and LV function parameters existed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the parameters of LV function are affected by individual differences [ 46 , 47 ], we analyzed the PCAT and LV function parameters by partial correlation analysis to exclude the effects of interference factors. There was no correlation between PCAT and LV function parameters, but a significant correlation between FAI and LV function parameters existed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the parameters of left ventricular function are affected by individual differences [32,33] , we analyzed the PCAT and left ventricular function parameters by using partial correlation analysis to exclude the effects of interference factors. There was no correlation between PCAT and left ventricular function parameters, but a signi cant correlation between FAI and left ventricular function parameters.…”
Section: Discussionmentioning
confidence: 99%
“… 161 , 162 , 163 , 164 One of the most interesting findings from the CARDIA study is that surgical menopause and age at natural menopause after 45 years were not strong predictors of CVD risk factors, subclinical atherosclerosis, or left ventricular indexes once presurgical or premenopausal risk factors were considered. 165 , 166 , 167 , 168 The CARDIA study's reproductive aging reports complement those from studies that enrolled perimenopausal women, such as the SWAN (Study of Women Across the Nation), or perimenopausal and postmenopausal women enrolled in cardiovascular cohorts, such as the ARIC (Atherosclerosis Risk in Communities Study) and MESA (Multi‐Ethnic Study of Atherosclerosis). 169 , 170 The CARDIA study and SWAN have both reported that risk factors are generally less favorable in the postmenopausal period than in the premenopausal period.…”
Section: Reproductive Aging and Menopausementioning
confidence: 99%